2017
DOI: 10.1080/14786419.2017.1366478
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing the interplay between miR-1275 and IGF2BPs by Tamarix articulata and quercetin in hepatocellular carcinoma

Abstract: Insulin-like growth factor-2 binding proteins (IGF2BPs) are oncogenic RNA-binding proteins, highly up-regulated in HCC, and were recently validated as direct targets of the tumour suppressor miR-1275. It is worth noting that around 47% of FDA approved anticancer drugs are derived from plants. Modulation by miRNAs and their cellular signalling cascades could constitute new pathways by which these phytochemicals exert their effects. This study aimed to investigate the potential use of Tamarix articulata, quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…For instance, up-regulation of miR-1275 regulated IGF2BPs to hinder tumour growth in hepatocellular carcinoma. 24 It was reported that miR-1275 exhibited its tumour suppressive role on nasopharyngeal carcinoma cells by down-regulating oncogenic HOXB5, whose expression was negatively related to miR-1275. 25 In our study, we found that miR-1275 was lowly expressed in glioma and its up-regulation could suppress glioma cell function including proliferation, migration and invasion, as well as induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, up-regulation of miR-1275 regulated IGF2BPs to hinder tumour growth in hepatocellular carcinoma. 24 It was reported that miR-1275 exhibited its tumour suppressive role on nasopharyngeal carcinoma cells by down-regulating oncogenic HOXB5, whose expression was negatively related to miR-1275. 25 In our study, we found that miR-1275 was lowly expressed in glioma and its up-regulation could suppress glioma cell function including proliferation, migration and invasion, as well as induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin antitumor effects have been described in different cancer types, including HCC [1]. In 25 of the articles included in the present review, quercetin efficacy as single treatment was evaluated employing different HCC study models [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46,48,49,[51][52][53][54]57]. Antiproliferative effect of this flavonoid alone has been demonstrated in several researches with in vitro models [22][23][24][25][26][27][30][31][32][33]35,38,46,48,49,[51][52][53][54], highlighting the HepG2 cell line as the most used in 21 of the 25 articles [24,25,<...>…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 99%
“…Among included articles, several of them determined effects of the flavonoid in different specific mechanisms [27][28][29]34,38]. These include inhibition of chymotrypsin-like activity of the proteasome, involved in proteasomal regulation of cancer signaling pathways [27,38]; rise of intracellular labile zinc, which has second messenger molecule activities in tumor cells [34]; and modulation of microRNAs expression, highly involved in cancer development and chemoresistance [63], leading to inhibition of the oncogenic RNA-binding proteins insulin-like growth factor-2 binding protein 1 and 3 (IGF2BP1 and IGF2BP3) through the upregulation of miR-1275 [29]. Another study published in 2018 employed quercetin to analyze adequacy of the cellular antioxidant (CAA) assay in HepG2 cells in order to determine the antioxidant activity of extracts from tree nuts [28].…”
Section: Antitumor Properties Of Quercetin As Single Agent Against Hccmentioning
confidence: 99%
“…However, quercetin dose-dependently reduced ROS and miR-21 and simultaneously upregulated PDCD4 (shown in Figure 2). 28 Detailed mechanistic insights revealed that miR-200b-3p switched symmetrical to the asymmetrical division of the cells by reversal of the Notch/Numb ratio and the inhibition of the self-renewal capacity. NF-κB was also inhibited by quercetin.…”
Section: Regulation Of Mirnas By Quercetin In Different Types Of Camentioning
confidence: 99%
“…Quercetin significantly enhanced miR-1275, whereas substantially downregulated IGF2BP1 and IGF2BP3 levels in Huh-7 cells. 28 Detailed mechanistic insights revealed that miR-200b-3p switched symmetrical to the asymmetrical division of the cells by reversal of the Notch/Numb ratio and the inhibition of the self-renewal capacity. 29 The lower level of miR-200b-3p promoted Notch signaling and promoted daughter cells to become symmetrical in appearance whereas higher levels of miR-200b-3p exerted repressive effects on Notch signaling and promoted daughter cells to become asymmetrical.…”
Section: Quercetin In Different Types Of Cancersmentioning
confidence: 99%